Influence of the Level of the Development of Skills on Labour Potential, its Implementation and Choice of Work Position - Ustinova, Kseniya Aleksandrovna; Chekmareva, Yelena Andreyevna (Economy of Regions, 2016)
The article deals with the sociological assessment of the skills level and identification of its influence on some aspects of labour activity: the realization of labour potential, choice of the scope of activity, position and occupation. It suggests an approach based on the subjective evaluation of the population as an instrument of the skills level assessment. The received results are compared with the indirect estimates allowing to characterize some particular components of labour potential which are similar to the considered skills. A specific feature of the research is not only the determination of the professional sphere, occupation and position on the skills level, but also the accounting of the reverse effect. The methodological tools including the methods for the assessment of skills level, labour potential and extent of its implementation in a labour activity have been approved in the Vologda region. The study revealed that, at the present time, the most developed skills are the teamwork, communication and mutual understanding while the least developed ones are the initiative and creativity as well as ability to be retrained and readiness to increase the professional level. It shows that the employees of socially oriented spheres and also the representatives of state structures have more developed skills. At the same time, the development of innovative skills not only leads to the growth of labour potential, but also creates conditions for the employment in workplaces with higher skills requirements. The paper shows that higher skills level along with higher skills requirements leads to more complete implementation of cumulative potential in the labour activity. The received results can be used by regional authorities for the development of the analytical system of labour market, the development of labour force and the labour potential of the population.